2021
DOI: 10.1016/j.heliyon.2021.e08091
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with food insecurity in Latin America and the Caribbean during the first wave of the COVID-19 pandemic

Abstract: Objective We assessed the prevalence of food insecurity (FI) and its associated factors in Latin American and the Caribbean (LAC) early during the COVID-19 pandemic. Methods We performed secondary data analysis of a survey conducted by Facebook and the University of Maryland. We included adults surveyed from April to May 2020. FI was measured by concerns about having enough to eat during the following week. Sociodemographic, mental health, and COVID-19-related variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 24 publications
3
24
1
5
Order By: Relevance
“…Although, to date, no study has compared these differences, there may be several explanations. In a previous study by our group evaluating food insecurity in LAC in the first stage of the pandemic, it was found that food insecurity was higher in Peru than in Colombia (83.9 % vs 76.8 %, respectively), which may explain the results of the present study [30] . Similarly, the impact of the pandemic was different in the two countries, with the number of deaths registered until November 17, 2021, being more than 200 thousand in Peru [31] and about 128 thousand in Colombia [32] .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although, to date, no study has compared these differences, there may be several explanations. In a previous study by our group evaluating food insecurity in LAC in the first stage of the pandemic, it was found that food insecurity was higher in Peru than in Colombia (83.9 % vs 76.8 %, respectively), which may explain the results of the present study [30] . Similarly, the impact of the pandemic was different in the two countries, with the number of deaths registered until November 17, 2021, being more than 200 thousand in Peru [31] and about 128 thousand in Colombia [32] .…”
Section: Discussionsupporting
confidence: 61%
“…As in other LAC countries, some factors associated with the socioeconomic and psychological consequences of the pandemic reduce the non-intention of vaccination [13] . Indeed, aspects such as stress [13] , economic or food insecurity as a result of the economic crisis during the pandemic and especially during the first wave [30] , possibly created a state of alert and the desire for such a situation not to be repeated, being vaccination seen as an opportunity to achieve this [13] . Along the same line, adherence to community mitigation measures such as the use of masks and social distancing may reflect a higher likelihood of complying with vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the last section includes questions about the respondent’s occupation. This survey has been used to develop previous studies [ 17 , 18 , 19 , 20 , 21 , 22 ] and the survey methodology has been described in more detail elsewhere [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 pandemic has worsened food insecurity, and a recent study estimated that 75.7% of persons in Latin America and the Caribbean were food insecure, with populations in Venezuela, Nicaragua, and Haiti being most affected ( 12 ). Poor diets high in ultraprocessed foods coupled with physical inactivity during lockdowns are likely to worsen COVID-19 outcomes.…”
Section: Access To Nutritionmentioning
confidence: 99%